(untitled) (Itinera, 2022)
This essay examines the two stories about or related to the Sabbath which Walter Benjamin included in his essay commemorating the tenth anniversary of Kafka’s death. Both are pastiches of Hasidic stories, apparently written by Benjamin himself. The first is based on a legend about a princess who prepares a festive meal for her fiancé on Friday evening, as the Sabbath begins; and the second is about the Jews in a Hasidic village who have assembled on Saturday evening, as the Sabbath is about to end, telling their wishes to each other. These stories, the essay suggests, are not only important for assessing Benjamin’s reading of Kafka’s oeuvre, but must at the same time also be seen as an expression of Benjamin’s own, gradually developing understanding of the Messianic dimensions of his own philosophy of history.